2017
DOI: 10.1115/1.4037372
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Partial Addition of n-Butanol in Sunflower Oil Methyl Ester Powered Diesel Engine

Abstract: Research focused in the present paper to evaluate the combustion, performance, and emission characteristics of refined biodiesel (refined biofuel) such as sunflower oil methyl ester (SOME) with the partial addition of n-butanol (butanol) in it. Various characteristics of butanol–SOME blends with varying volume percentage of butanol such as 5, 10, 15, and 20 in butanol–SOME blends were compared with the characteristics of neat SOME (100%) and neat diesel (100%). It is investigated that with an increase in butan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Patil et al observed exactly similar experimental conditions to the current study of BTE and reported the same BTE considerations for neat rubber oil methyl ester at full load conditions, injected 23° before TDC. Patil and Patil observed similar effects and reported them. The brake thermal efficiency is shown to improve as the load on the diesel engine increases for pure sunflower oil methyl ester at 100% load, injected 23° before TDC.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Patil et al observed exactly similar experimental conditions to the current study of BTE and reported the same BTE considerations for neat rubber oil methyl ester at full load conditions, injected 23° before TDC. Patil and Patil observed similar effects and reported them. The brake thermal efficiency is shown to improve as the load on the diesel engine increases for pure sunflower oil methyl ester at 100% load, injected 23° before TDC.…”
Section: Resultssupporting
confidence: 62%
“…Refined (esterified) biodiesel, such as thumba methyl ester (TME), which is readily available in India, according to the literature, could be a potential alternative sustainable fuel to unrefined thumba oil for diesel engines. However, the consequences of combusting TME/diesel blends made with nanocatalysts in a diesel engine have yet to be described in the literature. So far, the effects of combusting blends of fatty acid methyl ester prepared using homogeneous catalysts like NaOH or KOH and diesel in the diesel engine have been reported. Therefore, the current study is “first of its kind,” which reports the effects of combusting blends of fatty acid alkyl ester prepared using a nanocatalyst and diesel in the diesel engine. However, there is currently no study to support the use of heterogeneous catalysts in the hydrodynamic cavitation method for biodiesel synthesis. , The use of a photocatalyst in the synthesis of biodiesel has not yet been investigated .…”
Section: Introductionmentioning
confidence: 99%
“…Specific fuel consumption describes the amount of fuel required for deriving 1 unit of power and increases with increase in load condition because of high brake power at higher load conditions (Patil and Patil, 2018). Figures 11 and 12 illustrate the specific fuel consumption at varying loads for blend and ester samples.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, efforts are underway, to find alternative fuels for the diesel engine vehicles [1,2]. Vegetable oils are a promising alternative to diesel [3][4][5][6]. Rudolf diesel confidently predicted that the diesel engines will be operated with vegetable oils since they have major advantages as a substitute for diesel.…”
Section: Introductionmentioning
confidence: 99%